A Facile and In‐situ Methanol‐mediated Fabrication of Low Pd Loading, High‐efficiency and Size‐selectivity Pd@ZIF‐8 Hydrogenation Catalyst. Issue 19 (19th August 2021) - Zhang, Fengwei; Liu, Mengmeng; Liu, Qiang; Li, Jingjing; Li, Boyang; Dong, Zhengping
Abstract: In‐situ encapsulation of tiny and well‐dispersed Pd nanoparticles (Pd NPs) in zeolitic imidazolate frameworks (ZIFs) was firstly achieved using a one‐pot and facile methanol‐mediated growth approach, in which methanol served as both solvent and a mild reductant. The microstructure, morphology, crystallinity, porosity as well as evolution process of the catalysts were determined by TEM, XRD, N2 adsorption and UV‐vis spectra. Due to the complete encapsulation of such Pd NPs combined with ultrahigh surface area and uniform microporous structure of ZIF‐8, the resulting Pd@ZIF‐8‐60 min nanocomposite exhibited more superior catalytic activity for olefins hydrogenation with TOF of 7436 h −1 and excellent size selectivity than previously reported catalysts. Furthermore, the catalyst displays excellent recyclability for 1‐octene hydrogenation and without any loss of the Pd active species. Abstract : A facile and in‐situ methanol‐mediated strategy was proposed to fabricate Pd@ZIF‐8 catalyst for efficient and size‐selectivity alkenes hydrogenation.